A 9-V/Lux-s 5000-frames - Krymski, A.I.
A high-responsivity 9-V/Lux-s high-speed 5000-frames/s (at full 512×512 resolution) CMOS active pixel sensor (APS) is presented in this paper. The sensor was designed for a 0.35-μm 2P3M CMOS sensor process and utilizes a five-transistor pixel to provide a true parallel shutter. Column-parallel analog-to-digital converter (ADC) architecture yields fast readout from pixels and digitization of the data simultaneously with acquiring a new frame. The chip has a two-row SRAM to store data from the ADC and read previous rows of data out of the chip. There are a total of 16 parallel ports operating up to 90 MHz delivering ∼1.3 Gpixel/s or 13 Gb/s of data at the maximum rate. In conclusion, a comparison between two high-speed digital CMOS sensor architectures, which are a column-parallel APS and a digital pixel sensor (DPS), is conducted.
Keywords: 0.35 micron; 13 Gbit/s.; 262144 pixel; 512 pixel; 90 MHz; CMOS sensor; Active pixel sensor; Column-parallel APS; Column-parallel analog-to-digital converter; Digital pixel sensor; High-speed digital CMOS sensor architectures; Parallel shutter; Readout; Two-row SRAM